Understanding the Driving Forces of China's Development: An Additional Perspective on the Miracles of China's Progress (Asian Journal of Social Science Studies, 2025)
China‟s remarkable transformation over the past four decades has captivated global attention, offering invaluable insights into rapid development dynamics. From a predominantly agrarian economy in the late 1970s, China has emerged as an international industrial and technological powerhouse, achieving unprecedented economic growth, poverty reduction, and infrastructure modernization. This article explores the driving forces behind China‟s development through a unique personal lens: the “Three Ds and One M” framework: Discipline, Dedication, Attention to Detail, and Maintenance. Drawing on the author‟s ethnographic observations during three years of living and studying in China, complemented by visits to major cities such as Beijing, Shanghai, Guangzhou, Quzhou, Xian, Foshan, and Shenzhen, the article integrates personal observations with academic literature to provide a holistic understanding of China‟s progress. It situates China‟s development within its historical, global, and contemporary contexts, highlighting key milestones such as the reform and opening-up policy, the Belt and Road Initiative, and advancements in green technology. The analysis underscores the interplay of cultural values, institutional discipline, and technological innovation as critical enablers of sustainable development. This reflective study deepens our understanding of China‟s development model and offers lessons for other nations striving for sustainable and inclusive progress.